The Effect of Lithium Chloride on Neutrophil Activation on Exposure to Serum of Patients with Septic Shock - O. A. Grebenchikov; I. S. Kasatkina; K. K. Kadantseva; M. A. Meshkov; A. A. Bayeva (Общая реаниматология, 2020)
The aim of the study: to examine the anti-inflammatory effect of lithium chloride by exposing the human neutrophils to serum of patients with septic shock in vitro.Material and methods. The study was carried out on neutrophils extracted from the blood of 6 healthy donors, which were activated with serum from patients with septic shock. The neutrophil activity was evaluated with fluorescent antibodies to the CD11b and CD66b markers of degranulation. The level of human neutrophil apoptosis and necrosis was assessed 22 hours after extraction; quantitative assessment was made using annexin V and propidium iodide with flow cytofluorimetry. Intact and activated neutrophils were treated with 0.3, 3.0 and 9.0 mmol lithium chloride solution.Results. The level of CD11b expression on the surface of intact neutrophils (healthy donors) was 3434.50 [3311.0-3799.0] arbitrary fluorescence units (AFU). Incubation of neutrophils with serum of patients with septic shock increased CD11b expression 2.5 times to 8589.0 [7279.0-11258.0] AFU (P=0.005) vs intact leukocytes, and increased CD66b expression 2.7 times up to 27 600.0 [22 999.0-28 989.0] AFU ((P=0.005) vs intact neutrophils. Lithium chloride in concentrations of 0.3, 3.0 and 9.0 mmol in a dose-dependent manner reduced the level of expression of CD11b and CD66b molecules on the surface of activated neutrophils. Septic serum reduced spontaneous neutrophil apoptosis, and 3.0 mmol and higher lithium chloride solution induced spontaneous neutrophil apoptosis.Conclusion. Lithium chloride reduces the activation of neutrophils preactivated by serum of patients with septic shock, reduces expression of CD11b and CD66b molecules on the neutrophil surface, inhibiting the process of their activation (degranulation). Lithium chloride in concentration of 3.0 mmol and higher is able to induce spontaneous apoptosis of neutrophils activated by serum of patients with septic shock.